Sermaye piyasası aracı olarak gayrimenkul sertifikaları - Özcan, Fatma (My University, 2004)
Tezin konusu olan gayrimenkul sertifikaları, SPK'nın Seri:III No :19 tebliğinde düzenlenmiş bir menkul kıymettir. Gayrimenkul Sertifikasında ihraççı, ihraçtan elde ettiği fonla ihraca konu gayrimenkul projesini gerçekleştirir. Sertifika sahipleri projenin tamamlanmasından sonra, belirlenmiş sayıda sertifika ibrazı karşılığında, bağımsız bölüm talep hakkı kazanır. Yeterli sayıda sertifika ibraz edilmemesi ya da bağımsız bölüm mülkiyetinin talep edilmemesi durumunda, taşınmaz değerinde oluşan artıştan yararlanmayı sağlayacak şekilde talep edilmeyen gayrimenkullerin açık artırmayla satılması sonucu elde edilen bedelden sertifika başına düşen tutarı ya da sertifikada belirlenmiş olan anapara ve faizi isteme hakkı vardır. Sertifikada yer alan hak, gayrimenkulün mülkiyetinin devri talebini içerse de alacak hakkıdır. Proje tamamlanana kadar tapuya şerh verilmesi, yada taşınmaz üzerinde malikin haklarının kısıtlanması mevcut düzenlemeye göre mümkün değildir. Mevzuatta yapılacak değişikliklerle buna imkan verilmesi, menkul kıymet olarak sertifikaya güveni artıracaktır. Sertifikaya ilişkin düzenlemenin sadece tebliğde yer alması, gayrimenkul devri vaadinin şekle bağlı olarak yapılmasını düzenleyen kanun hükümleri karşısında sorun yaratmaktadır. Bu nedenle tebliğ hükümlerinin diğer kanunlarla uyumlu hale getirilmesi, sertifikanın en azından zorunlu içeriğiyle SerPK ya da TTK'da düzenlenmesi; Ticaret Sicil Tüzüğü, TMK, Tapu Kanunu ve Tapu Sicil Nizamnamesi gibi mevzuatla bağlantının sağlanması gereklidir. Tebliğde ihraççının edimi için banka garantisi zorunlu tutulmuştur. Tebliğle düzenlemenin yolaçtığı bir sorun da Bank K ile tebliğ hükümleri arasındaki uyumsuzluktan kaynaklanır. Bank K m. 12'de bankaların münhasıran gayrimenkul konusunda iş yapan gerçek ve tüzel kişilere kredi açamayacakları düzenlenmiştir. Bank K'da bunun istisnaları düzenlenmiş olmakla birlikte, bunların arasında gayrimenkul sertifikası yer almamaktadır. Bu durumda, mevcut mevzuata göre bankaların ihraççı lehine gayrinakdi kredi niteliğindeki garanti vermesi mümkün olmayacaktır. Tebliğle düzenlenmesinin yarattığı sorunlar dışında gayrimenkul sertifikası, yatırımcıya taşınmaz mülkiyeti kazanma veya taşınmazın değerindeki artıştan doğrudan yaralanma imkanı veren güvenceli ve yüksek getirili bir yatırım aracıdır. Real estate certificates which is the subject of the thesis is a real estate organized under the written notice of the SPK (Stock Market Board) Serial: III, No: 19. The issuer of the real estate certificate realizes the real estate project which is the subject of the issuance through the fund realized. Certificate holders acquire the right to demand of independent unit upon the issuance of certain certificates after the project completed. In case of non issuance of certain certificates or non demand of the independent unit ownership then has the right of demand of the capital and interest over the certain amount or amount per certificate over the amount realized as the result of the real estate sold through public auction which have not been demanded in a manner to get the benefit from the increase of the value of the real estate. Whether the right meant by the certificate contains the transfer of the ownership of the real estate, such credit is the true right. Placing a restriction on the title deed or placing a restriction on the rights of the owner until the end of the project is not possible in accordance with the already existed regulations. Making it possible through the amendments on the regulations will strengthen the reliability of the certificate. Placing the arrangement only within the written notice regarding the certificate creates problem against the provisions of the law that organizes the performance of the real estate transfer pledge. Therefore, it is necessary to render the provisions of the written notice compliance with the other regulations, to put the certificate at least in an order with its compulsory content under the SPK or TTK (Turkish Trade Act) and provide a connection with the Commerce Registration Regulation, TMK, Title Deed Act and Deed Register Regulations. Written notice provides a bank guarantee as an obligation for the activity of the issuer. Another problem caused by such written notice has been sourced by the dispute between the Bank K and the provisions of the written notice. Bank K m.12 organizes that banks shall not provide credit to the true and judicial persons who work exclusively in the field of real estates. Although the exceptions have been organized by the Bank K, real estate certificate has not been mentioned. In this case, it is unlikely to provide a security in the form of non monetary credit in favor of the issuer by the banks in accordance with such regulation. Real estate certificate is a secure and highly benefitable instrument of investment which allows the investor to acquire the ownership right and get the benefits of increase in the value of the real estate directly except the problems caused by such written notice.
Keywords: Gayrimenkuller_Hukuk